2008
DOI: 10.1093/gerona/63.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Change in Expression During Replicative Aging in Saccharomyces cerevisiae

Abstract: Yeast replicative aging is a process resembling replicative aging in mammalian cells. During aging, wild-type haploid yeast cells enlarge, become sterile, and undergo nucleolar enlargement and fragmentation; we sought gene expression changes during the time of these phenotypic changes. Gene expression studied via microarrays and quantitative real-time reverse-transcription polymerase chain reaction (qPCR) has shown reproducible, statistically significant changes in messenger RNA (mRNA) of genes at 12 and 18-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
43
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 81 publications
(48 reference statements)
12
43
2
Order By: Relevance
“…1). Transcriptome analysis of 18 -20-generation-old wild-type cells was reported previously and showed that cellular aging is associated with a shift toward gluconeogenesis and energy storage and a response to genome instability (7,15). The transcripts at this age, however, might include information from dead cells or exclude information from lysed cells.…”
Section: Experimental Concepts For the Early Stage Of Replicativementioning
confidence: 93%
See 4 more Smart Citations
“…1). Transcriptome analysis of 18 -20-generation-old wild-type cells was reported previously and showed that cellular aging is associated with a shift toward gluconeogenesis and energy storage and a response to genome instability (7,15). The transcripts at this age, however, might include information from dead cells or exclude information from lysed cells.…”
Section: Experimental Concepts For the Early Stage Of Replicativementioning
confidence: 93%
“…In all cases, a shift from glycolysis toward gluconeogenesis and energy storage (glyoxylate cycle, lipid metabolism, and glycogen production) was observed in old cells. In addition, the expression of ribosome genes and genes involved in protein synthesis, folding, and degradation all decreased (14,15). Besides changes in metabolic gene expression, environmental stress response genes were induced in aged cells (7), although oxidative stress gene expression did not change (14).…”
mentioning
confidence: 94%
See 3 more Smart Citations